Analyzing and Comparing Successful Attempts According to Some Biomechanical Indicators Using Smart Analyses Technology of Olympic Lifts in Iraqi Elite Weightlifters - Omran, Kanaan; Al-Sudani, Ali (Journal of Physical Education, 2020)
The importance of the research lies in studying some biomechanical indicators using smart analyses technology of Olympic lifts of Iraqi elite weightlifters. The researchers used the experimental method on (8) Iraqi elite weightlifters of the seasons (2019 – 2020). Beast sensor weightlifting test was applied as well as snatch and clean and jerk achievement tests followed by the main experiments and the posttests.